Persistence and Exposure Assessment of Insecticide Indoxacarb Residues in Vegetables - Patra, Sandip; Das, Anupam; Rakshit, Rajiv; Choudhury, Suborna Roy; Roy, Shyamashree; Mondal, Tilak; Samanta, Arunava; Ganguly, Pritam; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Brestic, Marian; Skalicky, Milan; et al. (Frontiers in Nutrition, 2022)
Indoxacarb, a promising new generation insecticide, is gaining popularity among vegetable growers in West Bengal, India, for controlling a large number of insects. However, it may simultaneously also increase the risk of contamination in the edible portions of the vegetables. The present study was planned to analyse the persistence behaviour of indoxacarb in cabbages, tomatoes and soil. Moreover, indoxacarb residue contents were estimated to assess both the dietary and soil ecological risks associated with the application of this particular insecticide. The location of the study was important because the chosen state is the leading producer of vegetables in the country. Indoxacarb was found to dissipate quickly in the substrates, and the pre-harvest interval was very low. The findings indicate that both vegetables can be safely consumed one day after the final spray. However, the risk to soil algae is predicted to be unacceptably high, which needs to be studied extensively.